2009
DOI: 10.1061/(asce)hy.1943-7900.0000095
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Verification of Incomplete Solute Mixing in a Pressurized Pipe Network with Multiple Cross Junctions

Abstract: Water quality models based on accurate mixing data at cross junctions are important for estimating concentrations of chemical species in municipal water distribution systems. Recent studies indicate that the instantaneous complete ͑thus "perfect"͒ mixing assumption potentially can result in an erroneous prediction of water quality. The present study examines the updated "incomplete" solute mixing model at cross junctions in a network having multiple cross junctions. The model performance in predicting solute t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Researchers from the University of Arizona, in collaboration with the University of Korea, assembled a laboratory pipe model to demonstrate the differences between simulations with complete and incomplete mixing [20,21]. They built a 5 × 5 square network with nine CJs and 32 pipes of 0.016 m diameter.…”
Section: Incomplete Mixing Models (Imms)mentioning
confidence: 99%
“…Researchers from the University of Arizona, in collaboration with the University of Korea, assembled a laboratory pipe model to demonstrate the differences between simulations with complete and incomplete mixing [20,21]. They built a 5 × 5 square network with nine CJs and 32 pipes of 0.016 m diameter.…”
Section: Incomplete Mixing Models (Imms)mentioning
confidence: 99%
“…These solvers have been developed on the basis of the convenient but potentially erroneous assumption that solute mixing is complete and instantaneous at the pipe junctions. Figure 1 The performance of AZRED on a laboratory-scale water network has been experimentally examined and validated (Song et al 2009) and applied to a large-scale network ). The present study uses AZRED as the WQ modeling tool for providing the input data needed to carry out sensor network designs over two exemplary water networks.…”
Section: Incomplete Solute Mixing At Junctionsmentioning
confidence: 99%
“…where: i, link with flow leaving node k; I k , set of links with flow into k; L j , length of link; Q j , flow (volume/time) in link j; Q k,ext , external source flow entering the network at node k; and, C k , ext , concentration of the external source flow entering at node k. Several authors [25][26][27][28][29][30][31][32][33][34][35][36] have numerically and experimentally demonstrated that the mixing in these unions is far from being "complete and instantaneous". Most of these researches were based on physical experiments and simulations through Computational Fluid Dynamics (CFD) using tracers for the concentration distribution analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these researches were based on physical experiments and simulations through Computational Fluid Dynamics (CFD) using tracers for the concentration distribution analysis. Some researchers [26][27][28][31][32][33][34][35][36] implement experimental scale models of a cross-junction and tee junctions with different pipe diameters, which are driven by elevated tanks where tracer is injected into one of them. Once the mix of the flows was made, mixing coefficients were formulated based on their experimental measurements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation